2017
DOI: 10.1177/0886260517692333
|View full text |Cite
|
Sign up to set email alerts
|

When Bigger Is Better: Household Size, Abuse Injuries, Neglect, and Family Response in Novosibirsk, Russia

Abstract: Although previous research has demonstrated larger households to be at higher risk of physical abuse and neglect of children, we argue that unilateral conceptualization of larger households as a risk factor is inappropriate. Application of resource dilution theory must capture the possibility that larger families may have more members with both the agency and will to intervene against child maltreatment. We hypothesized a negative interaction between household size and protective informal social control by fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“… 22 23 However, Emery and colleagues argue that it is not the family size, but the willingness of family members to act against child abuse on witnessing an event, that determines the likelihood of the child in the family experiencing abuse. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 22 23 However, Emery and colleagues argue that it is not the family size, but the willingness of family members to act against child abuse on witnessing an event, that determines the likelihood of the child in the family experiencing abuse. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that the frequency of neglect perpetration would likely be less if more adult family members intervene to safeguard children from neglect. Previous evidence, based on non‐neglect measures of informal social control, showed that expectations for informal social control (Guterman et al, 2009; Kim & Maguire‐Jack, 2015) and protective informal social control of physical abuse (Emery et al, 2020) were associated with less neglect. Results from this study reiterate this evidence in the Ghanaian context, but with an important advancement.…”
Section: Discussionmentioning
confidence: 97%
“…abuse(Emery et al, 2020) were associated with less neglect. Results from this study reiterate this evidence in the Ghanaian context, but with an important advancement.The use of a context-based and neglect-specific model of informal social control in neglect (measured by the ISC_CM2 scale,Abdullah & Emery, 2022b) brings precision to the study of informal social control in neglect.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Working outside one’s home area is a sign of being independent of the local context and associated with enhanced livelihood stability. Further, both marital status and household size have been regarded as important in the division of household labor and family support [ 8 , 9 , 10 ]. With the steady increase in labor force participation of women, large household size and a high proportion of females in a household can diversify income sources.…”
Section: Introductionmentioning
confidence: 99%